'Unsophisticated and unsuited': Australian barriers to Pacific Islander immigration from New Zealand. (December 2014) - Hamer, Paul
In the early 1900s, and in spite of the principles of the White Australia policy, Australia was forced to treat Māori crossing the Tasman in largely the same way as Pākehā New Zealanders. This served, first, to encourage New Zealand to federate and, second, to maintain healthy trans-Tasman diplomatic relations. However, extending uninhibited rights of entry to Pacific Island (and Asian) New Zealanders long remained a bridge too far for Australia. This was a cause of increasing tension with New Zealand, which had embraced closer ties with the Pacific and had, from the 1960s, allowed the immigration of thousands of Pacific Islanders. As late as 1971, the Australian cabinet agreed that Pacific Islanders were too 'unsophisticated' and 'unsuited' to settle freely in Australia. The election of the Whitlam government in 1972, though, led to the abandonment of this and other final vestiges of the White Australia policy. However, in the four decades since, Australia has progressively curtailed the rights of New Zealand migrants entering the country. There is good cause to believe that Australian dissatisfaction with New Zealand's more liberal rules of entry for Pacific Island migrants is one of the reasons behind this.